Distinct brain and neurocognitive transformations after bariatric surgery: a pilot study - Roy, Bhaswati; Thedim, Mariana; Liew, Chiewlin; Kumar, Rajesh; Vacas, Susana (Frontiers in Neuroscience, 2024)
BackgroundObese patients have worse outcomes after surgery and are at increased risk for perioperative neurocognitive disorders (PND). Our aim was to detail the cognitive trajectories of patients undergoing bariatric surgery (BS) and map distinct structural brain changes using magnetic resonance imaging (MRI) to better understand the association between the vulnerable brain, surgery, and the arc of PND.MethodsProspective pilot study with longitudinal comprehensive cognitive assessments and MRI were performed on obese patients scheduled for BS. We analyzed baseline cognitive function and high-resolution T1-/T2-weighted brain images on 19 obese patients [age, 54 (9) years, BMI, 40 (36, 42) kg m−2] and compared with 50 healthy control subjects [age, 52 (6) years; BMI, 25 (24, 27) kg m−2]. Patients were evaluated within five days of BS (baseline), immediately after (within 48h), and follow up at six months.ResultsAt baseline, obese patients had significant brain tissue changes seen in MRI and decreased cognitive scores compared to controls (MoCA 26 vs 28, P = 0.017). Surgery induced further gray matter volume and brain tissue changes along with reduced cognitive scores within the immediate postoperative period (MoCA 26 vs 24, P < 0.001). At six months, we observed reversal of brain alterations for most patients and a concomitant rebound of cognitive scores to patient’s baseline status.ConclusionsBariatric surgery resulted in worsening of preexisting brain structural integrity and lower cognitive function for obese patients compared to baseline. These distinct brain lesions are consistent with specific domains of cognition. Most of these changes reverted to patient’s baseline condition within six months after surgery.